2006
DOI: 10.2225/vol9-issue3-fulltext-29
|View full text |Cite
|
Sign up to set email alerts
|

NaCl effects in Zea mays L. x Tripsacum dactyloides (L.) L. hybrid calli and plants

Abstract: High salt concentrations in soils negatively affect maize growth. Techniques such as remote hybridization and in vitro selection have been extensively used to accelerate breeding processes. In order to determine the usefulness of Tripsacum to improve salt tolerance in maize, the effects of NaCl, in vitro and in vivo, were evaluated in an intergeneric hybrid (MT) obtained from crossing Zea mays with Tripsacum dactyloides. Organogenic calli, induced from immature MT hybrid embryos, were exposed to different NaCl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 13 publications
0
9
0
5
Order By: Relevance
“…Rahman et al (2000) reported that maize cultivars were significantly more tolerant to salt stress at germination than at later stages of growth. In order to determine the usefulness of Tripsacum in improving salt tolerance in maize, and the effects of NaCl, in vitro and in vivo, Pesqueira et al, (2006) evaluated an intergeneric hybrid obtained from crossing Zea mays L. with Tripsacum dactyloides L.…”
Section: Resultsmentioning
confidence: 99%
“…Rahman et al (2000) reported that maize cultivars were significantly more tolerant to salt stress at germination than at later stages of growth. In order to determine the usefulness of Tripsacum in improving salt tolerance in maize, and the effects of NaCl, in vitro and in vivo, Pesqueira et al, (2006) evaluated an intergeneric hybrid obtained from crossing Zea mays L. with Tripsacum dactyloides L.…”
Section: Resultsmentioning
confidence: 99%
“…Intact root system was carefully uprooted to prevent breakage. The following parameters were recorded: Length of root and shoot (cm), Number of lateral roots, Number of leaves, Fresh weight of plant (g), Dry weight of plant (g) (Pesqeira et al, 2006).…”
Section: Growth Promotion Study Of Mung Beansmentioning
confidence: 99%
“…The results of these experiments are presented as tolerance index (Ti) where Ti0RLs/ RLc, where RLs stands for root length of plant grown in the presence of salt and RLc stands for root length of plants grown in the absence of salt. Rate of salt transfer from soil to plant (Tf 0NaCl in plant/ NaCl in soil), known as transfer factor was also calculated on the basis of salt content in plant and salt content in soil (Pesqueira et al 2006).…”
Section: Residual Nacl In Soilmentioning
confidence: 99%
“…This crushed plant material (20 mg) was then added to a mixture of HNO 3 and HClO 4 in the ratio of 87:13. The plant was then heated to 708C for about 4 h and then at 1008C for 3 h. This plant digest was then used for estimating absorbed Na through AAS (Shimadzu 600) (Pesqueira et al 2006).…”
mentioning
confidence: 99%